Sugar Functionalized Collagen Material for Local Modulation of Innate Immunity - Francesca Taraballi; Claudia Corbo; Julia Enterria‐Rosales; John Otto Martinez; Silvia Minardi; Laura Pandolfi; Xing Wang; Ennio Tasciotti; Kavindra V. Singh; Cesar A. Arias; Bruna Corradetti (Advanced Science)
Abstract Small alterations during the early stages of the innate immune response to an implant can drive large changes in adaptive immunity. Biomaterials for regenerative purposes can be engineered to modulate this immune response in beneficial ways. This study presents an innovative patch designed and functionalized to target the innate immunity at the implant site. Mannose moieties are incorporated into collagen patches, resulting in a technology called Local Immunotuning Patch (LIP), designed to directly interact with antigen presenting cells through their mannose receptor. In vitro, LIP shows anti‐inflammatory effects on bone marrow‐derived macrophages and inhibitory properties even on methicillin‐resistant bacterial strains. Subcutaneous implantation in mice reveals that LIP modulates multiple pathways related to innate and adaptive immunity, underscoring its role in shaping an immune‐engineered environment around the implant. These findings highlight the potential of this strategy to control the foreign body reaction at the implant site, making it applicable for various uses, including wound healing and surgical infection control in reconstructive procedures.